Gilded Identities: The Enigma of Ada Clare’s Golden Tresses and Their Role in Bleak House - Wang, Yuanyuan; Liang, Xiaohui (Journal of Theory and Practice of Social Science, 2024)
In Victorian novels, hair color carries significant symbolic meaning, often depicting contrasting characteristics among characters: blonde women typically represent purity and obedience, while women with darker hair symbolize rebellion and wickedness. In Bleak House, Ada Clair exemplifies middle-class identity and the ideal of the angel in the house. This study, situated within the cultural context of hair representations in Dickens’ novels, aims to explore why Ada is depicted as a pure woman with redemptive qualities within the middle class. Through a comparative analysis of Ada’s hair color alongside that of other female characters in this fiction, as well as her relationships with male characters, this article seeks to reveal how issues of gender and class intertwine and manifest in complex ways during this period.